Assessment of trauma scoring systems in patients subjected to exploratory laparotomy - FONSECA,MARIANA KUMAIRA (2020)
ABSTRACT Objective: to assess the epidemiological profile of patients undergoing exploratory trauma laparotomy based on severity and prognosis criteria, and to determine the predictive accuracy of trauma scoring systems in terms of morbidity and mortality. Methods: retrospective cohort study and review of medical records of patients undergoing exploratory laparotomy for blunt or penetrating trauma at the Hospital de Pronto Socorro de Porto Alegre, from November 2015 to November 2019. Demographic data, mechanism of injury, associated injuries, physiological (RTS and Shock Index), anatomical (ISS, NISS and ATI) and combined (TRISS and NTRISS) trauma scores, intraoperative findings, postoperative complications, length of stay and outcomes. Results: 506 patients were included in the analysis. The mean age was 31 ± 13 years, with the majority being males (91.3%). Penetrating trauma was the most common mechanism of injury (86.2%), predominantly by firearms. The average RTS at hospital admission was 7.5 ± 0.7. The mean ISS and NISS was 16.5 ± 10.1 and 22.3 ± 13.6, respectively. The probability of survival estimated by TRISS was 95.5%, and by NTRISS 93%. The incidence of postoperative complications was 39.7% and the overall mortality was 12.8%. The most accurate score for predicting mortality was the NTRISS (88.5%), followed by TRISS, NISS and ISS. Conclusion: the study confirms the applicability of trauma scores in the studied population. The NTRISS seems to be the best predictor of morbidity and mortality.